2016
DOI: 10.1038/nsmb.3218
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered proteomics reveals molecular switches dictating ligand-dependent EGFR trafficking

Abstract: A fascinating conundrum in cell signaling is how stimulation of the same receptor tyrosine kinase with distinct ligands generates specific outcomes. To decipher the functional selectivity of EGF and TGF-α, which induce epidermal growth factor receptor (EGFR) degradation and recycling, respectively, we devised an integrated multilayered proteomics approach (IMPA). We analyzed dynamic changes in the receptor interactome, ubiquitinome, phosphoproteome, and late proteome in response to both ligands in human cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
188
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(200 citation statements)
references
References 68 publications
12
188
0
Order By: Relevance
“…Rab7 has at least two phosphorylation sites (serine 72 and tyrosine 183), which can act as a negative regulator or modulate function. Indeed, phosphorylation at serine 72 acts as an 'off switch' for Rab7 as the phosphomimetic mutant was completely cytosolic (Shinde and Maddika, 2016), while phosphorylation at tyrosine 183 is required to mediate the degradation of the EGFR (Francavilla et al, 2016). Here, we demonstrate that palmitoylation also regulates the function of Rab7.…”
Section: Rab7 Post-translational Modificationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Rab7 has at least two phosphorylation sites (serine 72 and tyrosine 183), which can act as a negative regulator or modulate function. Indeed, phosphorylation at serine 72 acts as an 'off switch' for Rab7 as the phosphomimetic mutant was completely cytosolic (Shinde and Maddika, 2016), while phosphorylation at tyrosine 183 is required to mediate the degradation of the EGFR (Francavilla et al, 2016). Here, we demonstrate that palmitoylation also regulates the function of Rab7.…”
Section: Rab7 Post-translational Modificationsmentioning
confidence: 70%
“…We have demonstrated that Rab7 palmitoylation is required for the efficient endosome-to-TGN trafficking of the lysosomal sorting receptors. Recent studies have also shown how phosphorylation (Francavilla et al, 2016;Shinde and Maddika, 2016) and ubiquitination (Song et al, 2016) can regulate Rab7 function. Rab7 has at least two phosphorylation sites (serine 72 and tyrosine 183), which can act as a negative regulator or modulate function.…”
Section: Rab7 Post-translational Modificationsmentioning
confidence: 99%
“…Such deep and broad PTM site coverage normally requires application of specific enrichment strategies in a sequential manner and extensive MS analysis time (Francavilla et al., 2016, Mertins et al., 2013, Swaney et al., 2013), but comes for free with the proteomics workflow presented here. This multi-shot proteomics strategy opens the possibility to study many PTMs simultaneously and estimate their stoichiometry directly (Olsen and Mann, 2013), enabling investigations of PTM crosstalk, an emerging theme in biology (Hunter, 2007), thus providing biological insights into the integrated and complex cell signaling layers.…”
Section: Discussionmentioning
confidence: 99%
“…All EGFR agonists induce receptor internalization, but alterations in receptor ubiquitinylation, recycling, or degradation of endocytosed receptors may be important. Indeed, differences in all of these activities have been reported across EGFR ligands (Francavilla et al, 2016; Roepstorff et al, 2009). The issue is not simply one of receptor recycling versus degradation, however; EGFR activated by either TGFα or epiregulin is internalized and recycled (Roepstorff et al, 2009), yet TGFα resembles EGF rather than epiregulin in its signaling kinetics (Figure 7C).…”
Section: Discussionmentioning
confidence: 99%